Photodissociation Mechanism Study of 1, 3-Dibromopropane using Theoretical Calculations - A-Hussien, Roaa; A-Ali Drea, Abbas (Al-Qadisiyah Journal of Pure Science, 2018)
A simulation study has been conducted by using Quantum calculation methods like DFT, Ab-initio and semiempirical methods to estimate the photolysis mechanism for 1,3-dibromopropane in the gas phase and its effect on the ozone layer. Energetic properties have been calculated like total energy and thermodynamic functions (G, S, Hf) for all chemical species that’s participate in the suggested reaction mechanism. Geometry optimized and single point calculation has been done to understand the configuration interaction singly excited state for three different conformations of 1, 3-dibromopropane which is found that the C2 isomer is the most stable with total energy being equal to -26652.031 kCal mol-1. Molecular orbital and their energy gap has been calculated using Ab initio//6-311G* and Beak 88 LYP//3-21G(d) level. The cleavage occurs at a wavelength equal to 442.571 nm and yields the 3-bromopropyl and bromine radical with activation energy equal to 98.624 kCal mol-1 calculated by using MNDO/d method. The 3-bromopropyl radical undergoing secondary dissociation through second C-Br bond to give the cyclopropane molecule as a final product with an energy barrier equal to 68.83 kCal mol-1.